Carcinoma ex pleomorphic adenoma of the parotid gland with cardiac metastasis - Bhandari, Anuja; Karki, Shovana; Sayami, Geeta (Journal of Pathology of Nepal, 2018)
Pleomorphic adenomas are the most common neoplasms of the major salivary glands. They are also known as benign mixed tumors because of the presence of both epithelial and mesenchymal elements. In parotid gland, approximately 65%-75% of tumors are pleomorphic adenomas. In parotid gland, usually it occur lateral to the plane of facial nerve. They present in middle aged patients as well defined, solitary, painless mass and are slow growing tumors. Few subset of tumors may undergo malignant transformation. Carcinoma ex pleomorphic adenoma is a rare and aggressive malignancy that arises from primary or recurrent pleomorphic adenoma. It occurs in 6% of all pleomorphic adenomas. Diagnosis of malignancy and treatment is largely based on pathologic and radiographic features. Distant metastases have been reported mainly in the lung. . We present an unusual case of 68 yrs female patient with carcinoma ex pleomorphic adenoma of the parotid gland with cardiac metastasis.